Resepsi Fungsional Al-Qur’an dalam Tradisi Keagamaan Lokal: Studi atas Tradisi Roah Kemalik pada Masyarakat Rembiga, Nusa Tenggara Barat - Anshori, Muhammad Helmi; Muhaimin, Abdul; Azmi, Aulul; Fathoni, Ahmad (UIN Sultan Syarif Kasim Riau, 2025)
This article aims to examine how the Rembiga community in West Nusa Tenggara receives and interprets the verses of the Qur’an within the Roah Kemalik tradition, which is deeply embedded in their social and cultural life. The Roah Kemalik tradition developed from the spread of Islam by figures such as Sunan Prapen and Ratu Ambiya and consists of rituals involving the recitation of Qur’anic verses believed to offer protection from disasters and calamities. This study employs a qualitative approach with a descriptive analytical method to elucidate the meanings and social functions of this tradition. The research questions addressed in this study are as follows: First, how is the Qur’an understood by the Rembiga community within the Roah Kemalik tradition? Second, in what forms is the reception of the Qur’an manifested in this tradition? The study concludes that the Rembiga community regards the Qur’an as sacred and deserving of sanctification. This tradition also serves as a process for the transmission and transformation of knowledge and practices that have existed since the arrival of Islam on Lombok Island. Generally, they interpret the Qur’an as a form of tafa’ul (a sign of good fortune); consequently, the meanings that emerge do not always align logically with the original intent of certain verses. The Roah Kemalik tradition is also grounded in several hadiths of the Prophet that legitimize the practice, which has been inherited and preserved by community authorities. This study affirms that the Roah Kemalik tradition is a dynamic social construct that harmonizes Islamic teachings with local culture, thereby shaping the religious identity of the Rembiga community to this day. Abstrak: Artikel ini bertujuan untuk mengkaji bagaimana masyarakat Rembiga, Nusa Tenggara Barat menerima dan memahami ayat-ayat Al-Qur’an dalam tradisi Roah Kemalik yang melekat kuat dalam kehidupan sosial dan budaya mereka. Tradisi Roah Kemalik berkembang mulai dari penyebaran Islam oleh tokoh-tokoh seperti Sunan Prapen dan Ratu Ambiya’, meliputi ritual pembacaan ayat-ayat Al-Qur’an yang diyakini memberikan perlindungan dari bencana dan musibah. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif analitis untuk mendeskripsikan makna dan fungsi sosial tradisi tersebut. Pertanyaan yang ingin dijawab adalah: Pertama, bagaimana Al-Qur'an dipahami oleh komunitas Rembiga dalam tradisi Roah Kemalik? Kedua, dalam bentuk apa penerimaan komunitas Rembiga dalam tradisi Roah Kemalik? Studi ini menyimpulkan bahwa komunitas Rembiga memandang Al-Qur’an sebagai sesuatu yang suci dan harus disucikan. Tradisi ini juga merupakan proses transmisi dan transformasi pengetahuan serta praktik yang telah ada sejak kedatangan Islam di pulau Lombok. Mereka umumnya memahami Al-Qur’an sebagai bentuk tafa’ul (tanda keberuntungan), sehingga dalam praktik yang dilakukan oleh masyarakat Rembiga, makna yang terkadang muncul tidak selalu sejalan secara logis dengan maksud asli ayat tertentu. Tradisi Roah Kemalik ini juga didasarkan pada beberapa hadis Nabi yang melegitimasi tradisi tersebut dan telah menjadi praktik yang diwariskan serta dilestarikan oleh otoritas masyarakat. Studi ini menegaskan bahwa tradisi Roah Kemalik merupakan konstruksi sosial dinamis yang mengharmoniskan antara ajaran Islam dan budaya lokal, membentuk identitas keagamaan masyarakat Rembiga hingga saat ini.